2003
DOI: 10.1103/physrevb.68.241309
|View full text |Cite
|
Sign up to set email alerts
|

Quantum magneto-oscillations in a two-dimensional Fermi liquid

Abstract: Quantum magneto-oscillations provide a powerfull tool for quantifying Fermi-liquid parameters of metals. In particular, the quasiparticle effective mass and spin susceptibility are extracted from the experiment using the Lifshitz-Kosevich formula, derived under the assumption that the properties of the system in a non-zero magnetic field are determined uniquely by the zero-field Fermi-liquid state. This assumption is valid in 3D but, generally speaking, erroneous in 2D where the Lifshitz-Kosevich formula may b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 26 publications
5
64
0
Order By: Relevance
“…Due to this cancelation, the exponential factor in A 1 does not contain terms of order T 2 ln T . A more detailed analysis [57], shows that T 2 terms are also absent, i.e., both quadratic terms and quadratic-times-log terms in the self-energy (and thus the linear-in-T effective mass [Eq. (3.40) ]) are not observable in a magneto-oscillation experiments.…”
Section: F Amplitude Of Quantum Magneto-oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this cancelation, the exponential factor in A 1 does not contain terms of order T 2 ln T . A more detailed analysis [57], shows that T 2 terms are also absent, i.e., both quadratic terms and quadratic-times-log terms in the self-energy (and thus the linear-in-T effective mass [Eq. (3.40) ]) are not observable in a magneto-oscillation experiments.…”
Section: F Amplitude Of Quantum Magneto-oscillationsmentioning
confidence: 99%
“…(3.45) is then only applicable as long as oscillations of the thermodynamic potential are exponentially small due to either finite temperature and/or disorder. In this paper we disregard effects of disorder (considered recently in [57]), thus the amplitude is only controlled by the finite temperature. In this case, the restriction of the small amplitude in its turn implies that the sum over Matsubara frequencies in (3.45) can be truncated to only the n = 0 term.…”
Section: F Amplitude Of Quantum Magneto-oscillationsmentioning
confidence: 99%
“…In recent years a number of caveats concerning the applicability of such a procedure to strongly interacting 2D systems have appeared. 54 In particular, Martin et al 55 have shown that the interplay between electron-electron interactions and electronimpurity scattering leads in 2D to an effective temperaturedependent Dingle temperature with a leading lowtemperature behavior of the type T D ͑T͒ ϰ T ln T. The need for the introduction of a temperature-dependent Dingle parameter in strongly coupled Si-MOSFETs has been emphasized in Ref. 48, where a linear T D ͑T͒ was used to fit the longitudinal magnetoresistance data.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown theoretically [48][49][50] that in a large field and temperature range the product µT D can be approximated by the product of the bare cyclotron mass µ 0 and Dingle temperature T D0 in the absence of electronphonon scattering. While the case of electron-electron interactions is less studied in this respect, Martin et al [51] have proposed that the same compensation should hold for any inelastic processes, including the electronelectron scattering.…”
Section: Resultsmentioning
confidence: 99%